Impact of Digital Learning Tools on Student Engagement and Achievement - Uzorka, Afam; ODEBIYI , Omotoyosi Aishat (RADINKA JAYA UTAMA PUBLISHER, 2025)
The integration of digital learning tools in higher education has transformed online learning, enhancing student engagement and academic performance. This study investigates the impact of digital learning tools such as Learning Management Systems (LMS), interactive simulations, and gamified content on student engagement and achievement in online courses. A qualitative research design was employed, involving semi-structured interviews with 52 lecturers from 12 universities in Uganda. Thematic analysis revealed six key findings: Digital tools enhance student engagement through interactivity, they help bridge the gap between theory and practice, they positively impact academic achievement, they facilitate communication between students and lecturers, Gamification increases student motivation, and they promote student autonomy in learning. The study concludes that digital tools significantly improve online education, but challenges such as limited internet access and digital literacy remain. It recommends improving digital infrastructure, providing faculty training, and integrating interactive digital tools to enhance student engagement and learning outcomes.